Theory of self-adjoint extensions of symmetric operators. entire operators and boundary-value problems - Gorbachuk, V. I.; Gorbachuk, M. L. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This is a brief survey of M. G. Krein’s contribution to the theory of self-adjoint extensions of Hermitian operators and to the theory of boundary value problems for differential equations. The further development of these results is also considered.